Decision triggers are a critical part of evidence-based conservation. (March 2016) - Cook, Carly N.; de Bie, Kelly; Keith, David A.; Addison, Prue F.E.
Abstract: Conservation managers face complex decisions about if, when and how to intervene in managed systems. To support these decisions, approaches are needed that utilise the best available evidence to guide actions when a system is moving into an undesirable state. Assigning some form of critical threshold that if crossed would trigger action (a decision trigger) is growing in favour in the scientific community. Likewise, there is increasing interest from the conservation management community in using decision triggers as part of evidence-based management. In this article, we reinforce calls for the use of decision triggers and highlight how they can complement many approaches for evidence-based conservation. There are many benefits to using decision triggers to link evidence to action. For management organisations, decision triggers offer a way to improve the clarity and transparency of management decisions. There has been recent progress in developing methods to set robust decision triggers that utilise rigorous biological monitoring data, such as receiver operating characteristic curves, control charts and participatory modelling. When monitoring data are not readily available, approaches that set decision triggers based on utility thresholds (i.e., value-based judgements) or expert elicitation methods, and refine trigger points over time, hold promise. Despite the many benefits, there remain challenges for both developing and implementing decision triggers. There is a pressing need for a process that can guide organisations in setting defensible decision triggers based on the best available science, and that can be used for a wide range of management contexts. We believe decision triggers can be integrated into existing management processes within organisations to improve decisions about when and how to act to protect biodiversity, and to support managers to achieve evidence-based conservation. Highlights: Decision triggers are important for evidence-based conservation to make decisions about when and how to intervene in systems Decision triggers are complementary to existing approaches to evidence-based conservation but fill a gap linking evidence to action Both managers and scientists support decision triggers because they structure decision-making and make it transparent A portfolio of methods are needed to develop robust decision triggers that can be applied to a range of management contexts